RELATIONSHIP BETWEEN COMPUTATIONAL THINKING AND NUMBER SENSE ABILITY AMONG FIFTH-GRADE STUDENTS IN BANDUNG INDONESIA - Nessa, Widya; Nugraha, Yuda Satria (PEOPLE: International Journal of Social Sciences, 2019)
Computational Thinking is the skill set of the 21st century that involves logical and algorithmic thinking approach. This skill is a highly valuable skill that has significant benefits associated with it. One of areas in which it may be applied is mathematics education. Number sense is one of major areas of emphasis in mathematics education that has many effects to mathematics achievement. While Computational Thinking focuses on algorithmic thinking, Number Sense contains problems in which both solution and method of solution are not obvious. This research aims to determine the relationship between Computational Thinking and Number Sense Ability of Bandungnese students in Grades 5. The subject of this research is from two different elementary schools (N=62). Data were collected separate tests on Computational Thinking and Number Sense. The test of Computational Thinking contains 3 problems with 7 questions both multiple choice and essay. Number sense test has 25 about multiple choice and short answer questions. Bandungnese students’ overall ability on Number Sense was lower than their performance on Computational Thinking. The results revealed correlation between these two aspects about 0.565 and provide that Bandungnese students have different levels on Computational Thinking and Number Sense Ability.